THE EFFECT OF WATER ON THE VISCOSITY OF SILICATE MELTS: A CONFIGURATIONAL ENTROPY APPROACH - AN EMPIRICAL METHOD OF PREDICTION - Davis M.J. (My University, 1999)
An analysis of the influence of water (<1500 ppmw) on viscosity in lithium disilicate melt has been conducted in light of the Adam-Gibbs (AG) structural relaxation model. Using information from prior relaxation studies and viscosity measurements, estimates were obtained for the physical parameters that appear in the AG model. The resulting viscosity predictions properly reflect the influence of hydroxyl on melt viscosity and the estimated configurational entropy for lithium disilicate is in accord with estimates for other compositions. The flexibility inherent in the Adam-Gibbs model allows for direct extension to multicomponent, high water content silicate melts given relevant thermodynamic and kinetic data.